Knowledge Sharing, Organizational Learning Capability, Open Innovation, and Business Performance: Evidence from Food and Beverage SMEs in Indonesia - Agus Setyo Pranowo; Towaf Totok Irawan; Zulkifli Musannip Efendi Siregar; R. Indra Kusuma Jaya (Universitas Pendidikan Ganesha, 2022)
The Covid 19 pandemic has made the business performance of the food and beverage industry decline. Therefore, innovation becomes very important to improve business performance. This study aims to analyze the effect of knowledge sharing and organizational learning capability on open innovation and its impact on SMEs’ business performance in the Context of the Food and Beverage SMEs. The objects in this study were employees in the food and beverage industry in Bogor. The number of questionnaires collected were 237 questionnaires. Therefore, the samples in the study were 237 Employees. The data analysis technique used is Structural Equation Modeling with the help of Amos software Version 23. The results show that knowledge sharing has a positive and significant effect on organizational learning capability, and knowledge sharing has a positive and significant effect on open innovation. Knowledge sharing and organizational learning capability have a positive and significant effect on open innovation. Knowledge sharing, organizational learning capability, and open innovation have a positive and significant impact on business performance. These findings of the results have important implications in the literature about the antecedent of SMEs’ performance that has not been previously tested. We suggest to the business owner in the Food and Beverage SMEs in Bogor to enhance the knowledge sharing practice, organizational learning capability, and open innovation to achieve good business performance.